Hydromechanical Rock Slope Damage During Late Pleistocene and Holocene Glacial Cycles in an Alpine Valley. Issue 8 (24th August 2020) - Grämiger, Lorenz M.; Moore, Jeffrey R.; Gischig, Valentin S.; Loew, Simon; Funk, Martin; Limpach, Philippe
Abstract: Subglacial water pressures influence groundwater conditions in proximal alpine valley rock slopes, varying with glacier advance and retreat in parallel with changing ice thickness. Fluctuating groundwater pressures in turn increase or reduce effective joint normal stresses, affecting the yield strength of discontinuities. Here we extend simplified assumptions of glacial debuttressing to investigate how glacier loading cycles together with changing groundwater pressures generate rock slope damage and prepare future slope instabilities. Using hydromechanical coupled numerical models closely based on the Aletsch Glacier valley in Switzerland, we simulate Late Pleistocene and Holocene glacier loading cycles including long‐term and annual groundwater fluctuations. Measurements of transient subglacial water pressures from ice boreholes in the Aletsch Glacier ablation area, as well as continuous monitoring of bedrock deformation from permanent Global Navigation Satellite Systems stations, help verify our model assumptions. While purely mechanical glacier loading cycles create only limited rock slope damage in our models, introducing a fluctuating groundwater table generates substantial new fracturing. Superposed annual groundwater cycles increase predicted damage. The cumulative effects are capable of destabilizing the eastern valley flank of our model in toppling‐mode failure, similar to field observations of active landslide geometry and kinematics. We find that hydromechanical fatigue is most effective acting in combination with long‐term loading and unloading of the slope during glacial cycles. Our results demonstrate that hydromechanical stresses associated with glacial cycles are capable of generating substantial rock slope damage and represent a key preparatory factor for paraglacial slope instabilities. Plain Language Summary: Glacial melt produces large amounts of water keeping water pressures at the base of alpine glaciers high. This meltwater in turn influences the groundwater table in adjacent valley flanks. Water seeps into the subsurface through joints and faults reducing the strength of these discontinuities. In a glaciated alpine valley, the position of the glacier changes over time and the groundwater table changes in accordance. Meanwhile, seasonal infiltration from snowmelt raises and lowers the water table in valley flanks, creating measureable movements. These changes in groundwater can alter the strength of a rock mass and together with the changing ice load generate damage in the floors and walls of alpine valleys. This damage helps prepare future slope instabilities, creating fractures that may ultimately define a landslide failure surface. We present new data and models from the Great Aletsch Glacier in Switzerland exploring our hypothesis that groundwater‐glacier coupled interactions are an important mechanism generating damage in alpine valley rock slopes. Our results show that higher water pressures reduce the strength of rock discontinuities and can result in failure, especially as glaciers retreat. This mechanism is an important part of the strength and stress changes in valley slopes that accompany glacial cycles. Key Points: Subglacial water pressures in ablation areas are high and vary with ice thickness, affecting the groundwater table in adjacent valley flanks Increasing groundwater pressure during glacier advance reduces effective stresses in joints, partly offsetting the increased ice load Hydromechanical coupled stresses during glacial cycles create and propagate fractures in rock slopes, preparing future instabilities